Premenopausal and Early Postmenopausal Trabecular Bone Score (TBS) and Fracture Risk: Study of Women’s Health Across the Nation (SWAN) - Greendale, Gail A. (Bone, 2020)
BACKGROUND. Evidence that trabecular bone score (TBS), an index of bone microstructure, is a risk factor for future fracture comes mainly from studies of late postmenopausal women. OBJECTIVE. To discern whether premenopausal TBS or early postmenopausal TBS predict fracture. DESIGN. A 22-year, prospective analysis from the Study of Women’s Health Across Nation. SETTING. Community-based cohort. PARTICIPANTS. 272 Black, 174 Japanese, and 364 White women MAIN OUTCOME MEASURES. Incident fractures: 292 in premenopausal sample and 141 in early postmenopausal sample. RESULTS. Separate Cox proportional hazard regressions modeled time to incident fracture as a function of TBS measured during premenopause or early postmenopause. Models were initially adjusted for age, race/ethnicity, SWAN clinical site, body mass index, use of calcium, vitamin D, bone beneficial or bone adverse medication. Next, we added lumbar spine (LS) or femoral neck (FN) bone mineral density (BMD) and, finally, history of prior fracture, to the models. For each standard deviation decrement in premenopausal TBS, fracture hazard was elevated by 17% (relative hazard [RH] 1.17 [95% CI, 1.02-1.35]); after adjusting for LS or FNBMD, the relation between premenopausal TBS and fracture was no longer statistically significant. There was a similar-magnitude, marginally statistically significant, association between early postmenopausal TBS and fracture, unadjusted for BMD (RH 1.15 [0.95- 1.39]). CONCLUSIONS. Variation in premenopausal TBS is related to fracture risk, but this association is not independent of BMD.